Service Quality Measurement in an IT organization: SERVQUAL Design and an AHP Model - Zhu, Ji Cheng (2006)
Measuring service quality is a challenge because customer satisfaction is determined by many intangible factors (Fitzsimmons and Fitzsimmons, 2001). SERVQUAL and AHP are the main two methodologies of measuring service quality. Since the end of 1980s SERVQUAL has been implemented widely in various service organizations. Due to some criticisms on SERVQUAL, the dissertation will also develop an AHP-based questionnaire for improvement. The AHP technique was developed by Saaty (1980, 1990, 1994), uses a process of pair wise comparisons to determine the relative importance of alternatives in a multi-criteria decision-making problem. (Chow & Luk, 2005). Therefore, the primary objective of this dissertation is to develop two kinds of service quality questionnaires respectively, then after real interview and comprehensive data analysis, the two methods are compared to make a conclusion.